Towards a theology of conflict transformation: a study of religious conflict in contemporary Nigerian society - Akanji, Israel Adelani (The University of Edinburgh, 2011)
Nigeria, the most populous country in Africa, is bedevilled with various conflicts which have been exacerbated by the multiplicity and diversity which characterize the nation. The country is a multi-ethnic, multicultural, multiregional and multi-religious society. And while such arrays of features are not peculiar to Nigeria, managing them has greatly propped up various conflicts, with religious conflict emerging as one of the most devastating of all. It would appear as though, more than any other single issue, religious conflict has become a threat to national cohesion, stability and development. It has led to fears, suspicions, unrest; mass displacement of people, destruction of lives and property; consequently leading to major set-backs for nation building. The three main religions of Nigeria are the Indigenous Religions, Islam and Christianity, with Islam and Christianity having almost equal strength of adherence. While the indigenous religions have generally been tolerant and accommodating of the two “guest” religions, contestations and incessant violent clashes have characterized the relationship between Muslims and Christians, particularly in Northern Nigeria, and this has been on the increase in frequency, intensity and sophistication. This situation has led to the emergence and deployment of numerous approaches towards transforming conflicts in order to ensure peaceful co-existence of all the people. The task of this thesis is to contribute practical, theological reflections to the ongoing search for how Nigeria will end the undesired religious conflict between Muslims and Christians and build a peaceful and harmonious society. To do this, John Paul Lederach’s conceptual framework for conflict transformation was adopted and explained in chapter one; and two religious conflicts which took place in the Northern Nigerian cities of Jos and Maduguri were empirically investigated through intensive fieldwork. A review of relevant literature was carried out in chapter two and an elaborate explanation of the socio-scientific and theological methodologies adopted for the research was presented in the third chapter. In order to establish the causes, manifestations and consequences of the conflicts, chapter four and five explored their remote and root causes. Because this research is grounded on the assumption that religion is not just a source of conflict, but a resource for peace, and on the contribution of faiths to contemporary public debates, it provides a new approach which challenges the religious institutions, particularly the Church, through its pastoral ministry, to become actively involved in the transformation of conflict in the nation. The research holds that the greatest contribution of religion to the quest to transform religious conflict in Nigeria is through a practical theology which should be demonstrated in both spirituality and strategy. As such, and based on empirical findings from the zones of conflict, a theology of hospitality is suggested in chapter six, as a gradual but effective method of transforming relationships between Christians and Muslims in Nigeria. While the approach does not preclude other approaches, it offers the enormous resources, possibilities and opportunities, ingrained within the religious domain for conflict transformation in contemporary Nigerian society. The strategies for achieving the desired transformation of the situation of conflict on short and long-term basis through the theology of hospitality are suggested in the seventh chapter.
Keywords: theology; conflict; transformation; Nigeria